PSYCHOSOCIAL COMPONENTS AND BEHAVIORAL EFFECTS ON OCCUPATIONAL HEALTH AND SAFETY OF MINING WORKERS IN NORTH MINAHASA REGENCY, NORTH SULAWESI PROVINCE - Lumintang, Genita G; Tielung, Maria Veronika J; Walangitan, Mac Donald Bertrand (International Journal of Research -GRANTHAALAYAH, 2022)
Occupational Health and Safety is currently not properly implemented in every company organization. There are still many accidents due to work in the workplace that cause death and physical disability. Psychosocial and behavioral factors play an important role related to employee safety and health. The physical work environment that is not supported by psychosocial components and employee behavior will ultimately make the occupational safety program unable to run optimally. This study aims to examine the effect of psychosocial and behavioral components on the occupational safety and health of mining workers in North Minahasa district, North Sulawesi province. The stages of the research method in this study used quantitative research methods, where this is a scientific method to obtain valid data with the aim of finding, proving, and developing knowledge so that it can be used to understand, solve, and anticipate problems in certain fields. In terms of its type, this research is an explanatory or explanatory research that explains the relationship between research variables, then determines the population and sample. The research design used is a type of survey research. The targeted output in this research is scientific articles in reputable international journals. The results of the study show that both the psychosocial component and the behavioral component partially have a significant positive effect. Simultaneously, the Psychosocial component and the Behavioral component have a significant positive effect.